Decision-Making Accuracy of CBM Progress-Monitoring Data. (February 2018) - Hintze, John M.; Wells, Craig S.; Marcotte, Amanda M.; Solomon, Benjamin G.
This study examined the diagnostic accuracy associated with decision making as is typically conducted with curriculum-based measurement (CBM) approaches to progress monitoring. Using previously published estimates of the standard errors of estimate associated with CBM, 20, 000 progress-monitoring data sets were simulated to model student reading growth of two-word increase per week across 15 consecutive weeks. Results indicated that an unacceptably high proportion of cases were falsely identified as nonresponsive to intervention when a common 4-point decision rule was applied, under the context of typical levels of probe reliability. As reliability and stringency of the decision-making rule increased, such errors decreased. Findings are particularly relevant to those who use a multi-tiered response-to-intervention model for evaluating formative changes associated with instructional intervention and evaluating responsiveness to intervention across multiple tiers of intervention.